gendered representations in Hawai'i's anti-GMO activism - Shaw, Amanda (Feminist review, 2016)
The aim of this article is to analyse some of the representations of intersectional gender that materialise in activism against genetically modified organisms (GMOs). It uses the case of Hawai'i as a key node in global transgenic seed production and hotspot for food, land and farming controversies. Based on ethnographic work conducted since 2012, the article suggests some of the ways that gender is represented within movements against GMOs by analysing activist media representations. The article shows how gender, understood intersectionally, informs possibilities for movement-identification, exploring how themes of motherhood, warrior masculinities and sexualised femininities are represented within these movements. The article suggests that some activist representations of gender invoke what could be considered as normative framings of gender similar to those seen in other environmental, food and anti-GMO movements. It is suggested that these gendered representations may influence and limit how different subjects engage with Hawai'i anti-GMO movements. At the same time, contextual, intersectional readings demonstrate the complex histories behind what appear to be gender normative activist representations. Taken together, this emphasis on relative norms of femininities and masculinities may provide anti-GMO organising with familiar social frames that counterbalance otherwise threatening campaigns against (agri)business in the settler state. Understood within these histories, the work that gender does within anti-GMO organising may offer generative examples for thinking through the relationships between gendered representations and situated, indigenous-centred, food and land-based resistances.